2024
DOI: 10.1001/jamanetworkopen.2023.50248
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Interpersonal Violence in Sport and Perceived Coaching Style Among College Athletes

Cheryl K. Zogg,
Edward B. Runquist,
Michael Amick
et al.

Abstract: ImportanceConcern about interpersonal violence (IV) in sport is increasing, yet its implications remain poorly understood, particularly among currently competing college athletes.ObjectiveTo document the self-reported prevalence of IV in college sports; identify associated risk factors; examine potential consequences associated with athletes’ psychosocial well-being, emotional connection to their sport, and willingness to seek help; and explore the associations between IV reporting and perceived variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“… 22 23 Experiences of interpersonal violence as a measure of abuse and harassment will be recorded. 24 In the ‘absence of mental ill-being’, general psychological well-being measures will include resilience and coping and psychological characteristics and skills (eg, the Nicholson McBride Resilience Questionnaire). 25–27 Overall measures of ‘perceived challenge and progress’ will be combined to assess the impacts of physical and mental chronic stressors on athletes over time.…”
Section: Methodsmentioning
confidence: 99%
“… 22 23 Experiences of interpersonal violence as a measure of abuse and harassment will be recorded. 24 In the ‘absence of mental ill-being’, general psychological well-being measures will include resilience and coping and psychological characteristics and skills (eg, the Nicholson McBride Resilience Questionnaire). 25–27 Overall measures of ‘perceived challenge and progress’ will be combined to assess the impacts of physical and mental chronic stressors on athletes over time.…”
Section: Methodsmentioning
confidence: 99%
“…In the USA, Zogg, et al [ 25 ] explored interpersonal violence in sports and perceived coaching styles among more than 4000 college athletes. The researchers found that almost 10% of the respondents reported having experienced at least one type of interpersonal violence during their college sports careers, even in the weeks immediately leading up to the study.…”
Section: Introductionmentioning
confidence: 99%